A tandem Prins spirocyclization for the stereoselective synthesis of tetrahydrospiro[chroman-2, 4′-pyran] derivatives. Issue 12 (26th February 2016) - Subba Reddy, B. V.; Hanuman Reddy, V.; Medaboina, Durgaprasad; Sridhar, B.; Rami Reddy, Y. V.
Abstract : A novel cascade process has been developed for the synthesis of tetrahydrospiro[chroman-2, 4′-pyran] derivatives by condensation of aldehydes with 2-(5-hydroxy-3-methylenepentyl)phenols using BF3 ·OEt2 under mild reaction conditions. Abstract : A novel cascade strategy has been developed for the synthesis of tetrahydrospiro[chroman-2, 4′-pyran] derivatives by condensation of aldehydes with 2-(5-hydroxy-3-methylenepentyl)phenol. The reaction proceeds smoothly in the presence of BF3 ·OEt2 under mild conditions in a highly stereoselective manner leading to a single diastereomer. This approach is simple and convenient for the synthesis of pharmacologically relevant spirochroman scaffolds.